Entre nós, oceano : a construção de um romance a partir da ideia de uma língua comum entre Brasil e Portugal - Cunha, Alexandra Lopes da (2020)
This thesis comprehends two complementary books: a creative one – a novel -, and a theoretical essay. The author´s intention in the elaboration of the essay was to offer a guide that could lead the reader through the fiction paths. The starting point is the author´s personal experience in the building of her novel, but other contributions, such as the experience and thoughts of well-known writers and literature theorists and thinkers are part of the reflection. The creative process is approached from the moment of conception, or “the initial spark”, in the words of Luiz Antonio de Assis Brasil, followed by a discussion of the concept of “the center” of a novel developed by Orhan Pamuk, and by an analysis of important aspects related to the construction of the fictional character. In the specific case of the novel here presented, aspects considered important for the development of the characters were also developed, such as the importance of the common language between Brazil and Portugal, mainly, the following topics: the idea of a common language, the identity construction, the importance of the language in the construction of an idea of oneself and of the others, aspects associated with Lusophony, and language sharing, as well as the construction of a Portuguese identity from literature. In this part of the essay, the contributions of the following thinkers were of vital importance: Zygmunt Bauman, Homi K, Bhabha, Eduardo Lourenço e Boaventura de Sousa Santos. Still regarding the subject of character´s development, the author discusses aspects of Art History and the female role in this universe, seeking to build a comprehensive overview of the participation and importance of female artists and their works, also including profiles of female artists from different eras and artistic skills.